Impacts of Microplastic Pollution on Soil Ecosystems and Agricultural Productivity - Haseeb Ullah Khan; Abdul Munim; Muhammad Umar Farooq; Nairab Ishaq; Muhammad Ali Waqar (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The pervasive use of plastics has resulted in widespread contamination of agricultural soils by microplastics (MPs,
Keywords: Microplastics; agricultural productivity; soil ecosystems; crop yields; plastic mulching; sewage sludge; irrigation; soil characteristics